Changes in The Statistical Properties of The Indonesian Stock Exchange Index Trough Five Different Time Periods Since 1998 Until 2016 - Nowo Riveli (Universitas Padjadjaran, 2017)
A simple method based on Kolmogorov-Smirnov Test were applied to the Indonesian Stock Exchange Index (IHSG) daily log return distribution to identify it’s time segmentation . Five separated periods were found from the overall data since July 1997 until May 2016. Distribution of the daily log return price from each time periods are characterized by two shape parameters of the fitted Levy-stable function, where the parameters are directly related to the variance and skewness of the distribution. The resulting time segmentations does indeed show systematic differences on the evolution of the daily index price, and the varying two fit parameters of the daily return distribution can be used to explain such diverse behavior.